Media Pembelajaran Pengenalan Huruf Abjad Jepang Dengan Animasi Interaktif Berbasis FlashMX - Supriyadi Sandi (Jurnal Komunikasi, 2021)
The InsCinema Course Education Institute has Japanese language course classes, the matriculation is done by collaborating this medium so that the course participants before entering their linguistics they have to learn with the introduction of these letters. The elements of using animation used in learning are able to convey complex concepts visually and dynamically. The form of media that is transformed into digital animation is able to attract the attention of students easily. Making with elements of this animated form can easily convey a message quickly compared to using other media. For the InsCinema course institution, the existence of this learning media as part of computerization is expected to be able to answer interactive learning needs that can display sounds, images, and information needed by course students. This multimedia letter recognition application is expected to be able to overcome the boredom of the course students and to make it easier for the tutor to complete the subject matter. Audio-visual and dynamic publications provided by animation technology can facilitate the process of applying concepts or demonstrations. So that the learning process starting from the atmosphere, technical use, user absorption and tutors who use it becomes easier